Optimization of reservoir operation at Klang Gate Dam utilizing a whale optimization algorithm and a Lvy flight and distribution enhancement technique - Lai V.; Huang Y.F.; Koo C.H.; Ahmed A.N.; El-Shafie A. (Taylor and Francis Ltd., 2023)
Development, operations and management of multi-objective reservoirs, is vital for timely water supply. Optimisation studies were done at the Klang Gate Dam (KGD) utilising standard optimisation and dynamic programming; according to the technology then. Taking it further, the KGD was studied using the nature-inspired meta-heuristic algorithms (MHAs). The Whale Optimisation Algorithm (WOA) solves complex technical issues. The Lvy flight and distribution (LFWOA) was incorporated to increase productivity at the KGD. The aim of this study to minimise KGD's water deficit with WOA and LFWOA. The study comprises of two sections. The first section examined observed monthly inflow, demand, and storage data from 2001 to 2019, whilst the second compares performances to established MHAs, from 1097 to 2008.In the first section, LFWOA and WOA reliability were 60.53 and 58.33 %,respectively. For 2010, both methods gave similar vulnerability value. The LFWOA scored 1.04 while the WOA scored 1. In second section, the LFWOA satisfied 69.70% of exact demand, while the WOA met 56.06%. LFWOA had attained the least shortage. The LFWOA algorithm was the most robust among the MHAs (1.88). In short, the LFWOA is better on the count of reliability, resilience, and scarcity scores. 2021 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.